2013
DOI: 10.12688/f1000research.2-23.v1
|View full text |Cite
|
Sign up to set email alerts
|

Neotendon infilling of a full thickness rotator cuff foot print tear following ultrasound guided liquid platelet rich plasma injection and percutaneous tenotomy: favourable outcome up to one year

Abstract: This is a case report on excellent clinical outcome and neotendon infilling at one year follow up in a degenerative rotator cuff full thickness tear following percutaneous tenotomy and platelet rich plasma injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There is only one case report on treatment of a full-thickness supraspinatus tear with percutaneous PRP injection. This demonstrated neotendon infilling and improvements in pain and function at 1 year but did not report on longer term functional or pain outcomes [61]. There is little evidence to support the use of PRP only in the percutaneous treatment of full-thickness supraspinatus tears.…”
Section: Stem Cells Internationalmentioning
confidence: 88%
“…There is only one case report on treatment of a full-thickness supraspinatus tear with percutaneous PRP injection. This demonstrated neotendon infilling and improvements in pain and function at 1 year but did not report on longer term functional or pain outcomes [61]. There is little evidence to support the use of PRP only in the percutaneous treatment of full-thickness supraspinatus tears.…”
Section: Stem Cells Internationalmentioning
confidence: 88%
“…19 Some studies have reported promising results when examining the effect of PRP in chronic tendinopathies. 16,[20][21][22][23][24][25] In a study comparing PRP with blinded sham saline injections, de Vos 26 and colleagues reported significant improvement in both saline and PRP groups that slightly favored the PRP subjects but not by a statistically significant margin. However, saline injection may not be the best control group because it is likely active for tendinopathy; injecting saline into the tendon alters the pressure-volume relationship in a given space, thereby disrupting pathologic vascular and neural ingrowth.…”
Section: Achilles Tendon Backgroundmentioning
confidence: 99%